Weight Addition on Pregnant Women as A Quality Predictor of Family Daily Food Consumption Pattern - awatiful azza; Cipto Susilo (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2019)
Introduction: Pregnancy is a physiological condition experienced by women after marriage. Physical changes and development occur in pregnant women can determine the health conditions of the mother and fetus. Nutritional status of the mother is one of an important key factors in pregnancy. The objective of this study determines the relationship between daily nutritional consumption of family and weight addition on pregnant. Methods: The design used in this study is correlational with cross sectional approach and the data obtained through questionnaires and documentary studies. Data analysis was carried out either quantitatively using Spearman rank or qualitative to deepen the findings in the field. Results: The results of this study found that the P-value 0.002 which means there is a relationship between the nutritional consumption with the nutritional status of pregnant women. The correlation coefficient was 0.309 which means a moderate relationship with positive correlation value implied that the better daily nutritional consumption of family, the higher nutritional status of pregnant women. Conclusions: Understanding the nutritional needs of pregnant women requires good cooperation between family and health workers.